Comparing the motivational underpinnings of sustainable consumption across contexts using a scenario-based approach - Doran, Rouven; Bø, Simen; Hanss, Daniel (Frontiers in Psychology, 2022)
A sample of tourists (N = 780) responded to a survey addressing purchasing intentions and consumption motives in relation to buying sustainable groceries at a local food market. These intentions and motives were contrasted for two consumption contexts: on vacation versus at home. An initial analysis of the data indicated that self-reported purchasing intentions were weaker for a vacation-scenario than for a home-scenario. Further analyses suggested that motives associated with purchasing intentions were not universal between the two contexts. At home, normative motives (i.e., good conscience) were positively associated with intentions, whereas other motives failed to explain significant variance (i.e., value for money, calm and safe, avoid boredom, pleasure, and good impression). On vacation, associations with intentions followed a similar pattern, except for the finding that hedonic motives (i.e., pleasure) added explanatory variance. Despite the increased importance of hedonic motives on vacation compared to at home, normative motives showed the strongest association with purchasing intentions in both contexts. The findings are discussed with reference to the literature on contextual discrepancies in environmental behaviour, while noting possible implications for promoting sustainable consumption among tourists.